Investigation of dual–pass inclined oscillating bed solar dryer for drying of non-parboiled paddy grains - Ganapathy, Ponnambalam Arul; Thulasi, Selvam; Kumar, Pitchaipillai; Veeranan, Arunprasad; Shaik, Saboor; Abbas, Mohammad; Rajendran, Parvathy; Khan, Sher Afghan; Saleel, Ahmed C (https://www.mdpi.com/journal/sustainability, 2022)
This Paper determines an experimental study of a dual-pass solar dryer with a bed tilt of 0.5° and varying the oscillating frequency of the drying chamber namely 1.25, 1.75, and 2.25 Hz for drying an agricultural produce namely non–parboiled paddy grains. The oscillations and bed tilt are provided to move the grains from entry to exit of the top bed and move down to the bottom bed and finally exit from the dryer. The new technology has been used in the solar dryer for drying agricultural produce as non–parboiled paddy grains to increase the quality and decrease the loss of the dried produce. The present dryer model was used for drying 45 kg of non–parboiled paddy grains from 19% (w.b) to the approved range of 12–14% of moisture content obtained in a single experimental day. The dried paddy grains obtained an average moisture content are 13.03, 13.22, and 13.51% at the frequency of oscillation of 1.25, 1.75, and 2.25 Hz, respectively. The maximum thermal and pick-up efficiency of the model was obtained at 1.00 p.m. in all cases. For the frequency of oscillation of 1.25, 1.75, and 2.25 Hz, the maximum dryer thermal efficiency was 44.47, 43.39, and 41.39%, respectively, and the maximum pick–up efficiency was 80.41, 79.19, and 76.21%, respectively. The optimum drying performance was obtained at the oscillating frequency of 1.75 Hz with the bed tilt of 0.5°